AN ANALYSIS OF TEACHERS’ PEDAGOGICAL COMPETENCE IN LESSON STUDY OF MGMP SMP MAJALENGKA - Raynesa Noor Emiliasari (STKIP Siliwangi, 2018)
This research reports an in-depth view of teachers’ pedagogical competence as they participated in the Lesson Study activities. In order to collect the data, observations, notes, videotaping and interviews were used to get comprehensive data in the field. It was revealed that there was a difference between senior and junior teachers in their pedagogical competence. Senior teachers had a better pedagogical competence in terms of: classroom management, understanding the students’ characteristics, curriculum development, lesson plan, and teachers’ talk. Meanwhile, junior teachers were good at: the use of ICT and the development of media in teaching. It was also discovered that both senior and junior teachers were still less in mastering the theory of basic principles in teaching and developing students’ potential. There was no reflective action in teaching and teachers’ less understanding in classroom action research were other factors that affect teachers’ pedagogical competence. It is suggested that in order to improve the quality of teaching, teachers’ pedagogical competence is very important to be improved. Keywords: Teachers’ Pedagogical Competence, Lesson Study